Democratizing Glacier Data – Maturity of Worldwide Datasets and Future Ambitions - Gärtner-Roer, Isabelle; Nussbaumer, Samuel U.; Raup, Bruce; Paul, Frank; Welty, Ethan; Windnagel, Ann K.; Fetterer, Florence; Zemp, Michael (Frontiers in Climate, 2022)
The creation and curation of environmental data present numerous challenges and rewards. In this study, we reflect on the increasing amount of freely available glacier data (inventories and changes), as well as on related demands by data providers, data users, and data repositories in-between. The amount of glacier data has increased significantly over the last two decades as remote sensing techniques have improved and free data access is much more common. The portfolio of observed parameters has increased as well, which presents new challenges for international data centers, and fosters new expectations from users. We focus here on the service of the Global Terrestrial Network for Glaciers (GTN-G) as the central organization for standardized data on glacier distribution and change. Within GTN-G, different glacier datasets are consolidated under one umbrella, and the glaciological community supports this service by actively contributing their datasets and by providing strategic guidance via an Advisory Board. To assess each GTN-G dataset, we present a maturity matrix and summarize achievements, challenges, and ambitions. The challenges and ambitions in the democratization of glacier data are discussed in more detail, as they are key to providing an even better service for glacier data in the future. Most challenges can only be overcome in a financially secure setting for data services and with the help of international standardization as, for example, provided by the CoreTrustSeal. Therefore, dedicated financial support for and organizational long-term commitment to certified data repositories build the basis for the successful democratization of data. In the field of glacier data, this balancing act has so far been successfully achieved through joint collaboration between data repository institutions, data providers, and data users. However, we also note an unequal allotment of funds for data creation and projects using the data, and data curation. Considering the importance of glacier data to answering numerous key societal questions (from local and regional water availability to global sea-level rise), this imbalance needs to be adjusted. In order to guarantee the continuation and success of GTN-G in the future, regular evaluations are required and adaptation measures have to be implemented.